Stainless steel for Ni brazing, joints, heat exchangers and water heaters

By optimizing the component composition of stainless steel to enhance Ni brazing properties, the challenges of corrosion resistance in water heaters and heat exchangers are addressed, allowing for reduced copper usage and improved manufacturing efficiency.

JP7667189B2Active Publication Date: 2025-04-22JFE STEEL CORP +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2023007684
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-01-20
Publication Date
2025-04-22
Estimated Expiration
2043-01-20

AI Technical Summary

Technical Problem

Existing stainless steels used in water heaters and heat exchangers exhibit insufficient nickel (Ni) brazing properties, leading to reduced corrosion resistance and increased risk of corrosion, especially in areas with low water purification capacity or high chloride exposure.

Method used

The development of a stainless steel with a specific component composition that optimizes the Ni content in relation to Si, Mn, Cr, and Al, satisfying the relationship Ni/(Si+Mn+0.08×Cr+Al)≧2.30, which enhances the Ni brazing properties by improving the wetting phenomenon between the stainless steel and the Ni brazing material.

Benefits of technology

This optimized stainless steel achieves excellent Ni brazing properties, with a spreading rate of the Ni brazing material of 150% or more, significantly reducing the need for copper in water heaters and heat exchangers, thereby lowering production costs and extending the lifespan of these components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667189000001
    Figure 0007667189000001
Patent Text Reader

Abstract

To provide a stainless steel with superior Ni brazability.SOLUTION: A stainless steel for Ni brazing has a properly controlled composition, satisfying the relationship of formula (1): Ni / (Si+Mn+0.08×Cr+Al)≥2.30 (1), where Si, Mn, Cr, Ni and Al each represent Si, Mn, Cr, Ni and Al content (mass%) in the composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to stainless steel for Ni brazing (hereinafter also simply referred to as stainless steel), a joined body, a heat exchanger, and a water heater. [Background technology]

[0002] Copper is used in large quantities in water heaters, including gas water heaters and electric water heaters. For example, copper pipes are widely used for the piping that carries the water and heat transfer medium used in water heaters. Also, from the perspective of protecting the global environment, environmentally friendly water heaters are becoming more and more popular. In these environmentally friendly water heaters, a secondary heat exchanger is used. Copper is also used in this secondary heat exchanger.

[0003] In recent years, the demand for copper for electric wires and conductors has increased due to the growing demand for power infrastructure in various countries and the shift to electric vehicles, resulting in a tight supply and demand situation for copper. The demand for copper is expected to continue to increase, and the price of copper is expected to rise accordingly. For this reason, there is a strong demand to reduce the amount of copper used in water heaters.

[0004] In light of this, there has been discussion about replacing the copper used in water heaters with other materials, in particular stainless steel, which is relatively inexpensive and has excellent corrosion resistance.

[0005] Here, the piping and heat exchanger parts of the water heater (hereinafter also referred to as the piping of the water heater) are mainly bonded and assembled by brazing. In general, the brazeability of stainless steel is inferior to that of copper. Therefore, stainless steel used in water heaters is required to have the same level of brazeability as copper.

[0006] As a technique related to the brazing of stainless steel, for example, Patent Document 1 describes: "An injector for direct injection internal combustion engines, in which the injector cup is copper brazed to a stainless steel pipe. A fuel rail, The stainless steel pipe is Formula I (Si%)≦3.75(C%)+0.37 (wherein (C%)≦0.08) (The combination of atomic symbol and % indicates the mass percent concentration of each atom in steel.) A fuel rail for a direct injection internal combustion engine, characterized in that it is made of austenitic stainless steel having a silicon concentration (Si%) and a carbon concentration (C%) that satisfy the above. has been disclosed.

[0007] In Patent Document 2, In weight percent, C: 0.06% or less, Si: 1.0-5.0%, Mn: 1.0% or less, P: 0.045% or less, S: 0.003% or less, Ni: 8.0-17.0%, Cr: 16.0-20.0%, Mo: 0.5-2.5%, Cu: 4.0% or less, N: 0.1% or less, and A: I: 0.2% or less, Nb: 0.2% or less, Ti: 0.2% or less, and one or more of these. +Cr+Mo≧20%, with the balance being Fe and unavoidable impurities. Cu brazing "This austenitic stainless steel is characterized by its excellent resistance to Cu grain boundary penetration during welding." has been disclosed.

[0008] In Patent Document 3, In mass%, C: 0.05% or less, Si: 1% or less, Mn: 1% or less, P: 0.045% or less, S: 0.005% or less, Ni: 1-6%, Cr: 18-24%, N: 0.05% or less, Nb: 7×(C+N) to 0.7%, the balance being Fe and unavoidable impurities, and the following (1) When the T value of the first term on the right side of the formula is changed in the range of 950 to 1200, the M value on the left side The content of each element on the right side of formula (1) is adjusted so that the value may be 1 to 25. Stainless steel for mounting. M=-0.22T+34.5Ni+10.5Mn+13.5Cu-17.3Cr-17.3S i-18Mo+475.5 ……(1) However, the element symbols on the right side of formula (1) represent the content of the corresponding element expressed in mass%. The values ​​of the quantities are substituted, in this case Cu and Mo, with 0 (zero) substituted for each." has been disclosed. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2020-2839 A [Patent Document 2] JP 2015-200023 A [Patent Document 3] JP 2010-65278 A Summary of the Invention [Problem to be solved by the invention]

[0010] Meanwhile, the piping of a water heater is required to be corrosion-resistant, especially high corrosion resistance depending on the region where it is installed. For example, in regions with low water purification capacity, tap water contains corrosive substances. In this case, there is a high risk of corrosion occurring inside the water heater. In addition, when the water heater is used in an environment where chlorides adhere, such as coastal areas, the shortening of the lifespan due to corrosion becomes an issue.

[0011] For this reason, when brazing pipes for water heaters, etc., it is desirable to use a brazing filler metal that has the same corrosion resistance as the base metal, stainless steel, such as a brazing filler metal containing Ni (hereinafter also referred to as Ni brazing filler metal).

[0012] In this regard, the techniques disclosed in Patent Documents 1 and 2 provide good brazing properties when using a Cu brazing material, but the brazing properties when using a Ni brazing material (hereinafter also referred to as Ni brazing properties) are not sufficient.

[0013] Moreover, the Ni brazeability was not sufficient even in the technology disclosed in Patent Document 3. Also, there were problems in terms of manufacturability, such as the need to go through a long heating step during production.

[0014] The present invention has been developed in view of the above-mentioned circumstances, and has an object to provide a stainless steel that has excellent Ni brazeability. Another object of the present invention is to provide a joint, a heat exchanger and a water heater using the above stainless steel.

[0015] Here, "excellent Ni brazeability" means that when the Ni brazing material is placed on the surface of the stainless steel test material and heated, the spreadability of the Ni brazing material is 150% or more. The spreadability of the Ni brazing material is calculated by the following formula. [Spreadability of Ni brazing material (%)] = [Circle equivalent diameter of Ni brazing material on the surface of the test material after heating (mm)] ÷ [Circle equivalent diameter of Ni brazing material on the surface of the test material before heating (mm)] × 100 The heating conditions for the Ni brazing material are as described in the Examples section below. [Means for solving the problem]

[0016] In order to achieve the above object, the present inventors have conducted extensive research and have obtained the following findings. (1) Brazing is a method of joining base materials by melting a brazing filler metal and utilizing the metallic bond that occurs between the brazing filler metal and the base metal, such as stainless steel (hereinafter simply referred to as the base material). Brazing is generally performed in a vacuum or in an atmosphere using an inert gas such as nitrogen or argon as a carrier gas. However, it is difficult to completely remove oxygen from the atmosphere. Therefore, an oxide film composed of oxides (of elements contained in the base material) is formed on the surface of the stainless steel base material. This oxide film inhibits the formation of a metallic bond between the brazing filler metal and the base material and the wetting of the brazing filler metal.

[0017] (2) Based on this, the inventors first investigated suppressing the formation of an oxide film by reducing elements such as Al that are particularly prone to forming an oxide film (hereinafter also referred to as easily oxidized elements) among the elements contained in the stainless steel base material. However, sufficient Ni brazeability could not be obtained by only reducing the easily oxidized elements.

[0018] (3) Therefore, the inventors conducted further experiments and studies on the composition of the stainless steel base material. As a result, they discovered that excellent Ni brazeability can be obtained by optimizing the composition by reducing easily oxidized elements, as well as by adding a certain amount of Ni, particularly by appropriately controlling the Ni content so as to satisfy the relationship of the following formula (1) according to the Si, Mn, Cr and Al contents. Ni / (Si+Mn+0.08×Cr+Al)≧2.30 ···(1) In the formula, Si, Mn, Cr, Ni, and Al are the contents (mass%) of Si, Mn, Cr, Ni, and Al in the composition, respectively.

[0019] The inventors consider the above reasons as follows. The wetting phenomenon can be understood from the bond energy between solid (base material) atoms and the bond energy between liquid (brazing material) atoms. In other words, the closer the bond energy between solid atoms and the bond energy between liquid atoms are, the better the liquid will wet the solid. These values ​​are determined primarily by the chemical composition of the material. In this regard, by optimizing the chemical composition of the stainless steel base material and satisfying the relationship in formula (1) above, the bond energy between solid atoms and the bond energy between liquid atoms will become closer. As a result, excellent Ni brazeability can be obtained. The present invention was completed based on the above findings and through further investigation.

[0020] That is, the gist and configuration of the present invention are as follows.

[0021] 1. In mass percent, C: 0.001 to 0.050%, Si: 0.01 to 0.50%, Mn: 0.01 to 0.50%, P: 0.050% or less, S: 0.010% or less, Cr: 16.00~22.00%, Ni: 3.00~15.00%, Al: 0.100% or less and N: 0.001 to 0.300%, and the balance being Fe and unavoidable impurities, A stainless steel for Ni brazing that satisfies the relationship of the following formula (1). Ni / (Si+Mn+0.08×Cr+Al)≧2.30 ···(1) In the formula, Si, Mn, Cr, Ni, and Al are the contents (mass%) of Si, Mn, Cr, Ni, and Al in the composition, respectively.

[0022] 2. The composition further comprises, in mass%, Mo: 3.00% or less Cu:3.00% or less, Ti: 0.50% or less, Nb: 0.50% or less, V: 0.20% or less, Zr: 0.10% or less, Sn: 0.50% or less, B: 0.0100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, Ta: 0.10% or less and REM: 0.10% or less 2. The stainless steel for Ni brazing according to claim 1, containing one or more selected from the following:

[0023] 3. The stainless steel for Ni brazing according to 1 or 2 above, A metal material; a joint of the Ni brazing stainless steel and the Ni brazing material that joins the metal material; A zygote that has the following functions.

[0024] 4. A heat exchanger having the joint described in 3 above.

[0025] 5. A water heater having the joint described in 3 above. Effect of the Invention

[0026] According to the present invention, a stainless steel with excellent Ni brazing properties can be obtained. Furthermore, it becomes possible to replace much of the copper used in water heaters, heat exchangers, etc. with the stainless steel of the present invention. As a result, it becomes possible to manufacture water heaters, heat exchangers, etc. that use significantly less copper, which is of great industrial benefit. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] [1] Stainless steel The stainless steel of the present invention will be described based on the following embodiments. First, the composition of the stainless steel according to one embodiment of the present invention will be described. Note that the unit of the content of elements in the composition is "mass%", and hereinafter, unless otherwise specified, it will be simply indicated as "%".

[0028] C: 0.001 to 0.050% Increasing the C content improves the strength of the steel, while decreasing it improves the workability. Here, the C content must be 0.001% or more to obtain sufficient strength. However, if the C content exceeds 0.050%, the workability decreases significantly. In addition, Cr carbides precipitate at the grain boundaries, causing sensitization and making the corrosion resistance more likely to decrease. Therefore, the C content is set to a range of 0.001 to 0.050%. The C content is preferably 0.003% or more. In addition, the C content is preferably 0.030% or less, and more preferably 0.020% or less.

[0029] Silicon: 0.01 to 0.50% Silicon is an element useful as a deoxidizer. Such an effect can be obtained with a silicon content of 0.01% or more. However, if the silicon content exceeds 0.50%, an oxide film is formed during brazing, and brazing properties are reduced. Therefore, the silicon content is set to a range of 0.01 to 0.50%. The silicon content is preferably 0.35% or less.

[0030] Mn: 0.01 to 0.50% Mn is an element that has a deoxidizing effect. Such an effect can be obtained with a Mn content of 0.01% or more. However, if the Mn content exceeds 0.50%, Mn oxide is generated on the surface of the stainless steel during brazing, and the brazeability decreases. Therefore, the Mn content is set to a range of 0.01 to 0.50%. The Mn content is preferably 0.25% or less, and more preferably 0.20% or less.

[0031] P:0.050% or less P is an element that is inevitably contained in steel. Excessive P content reduces weldability and makes intergranular corrosion more likely to occur. This tendency becomes more pronounced when the P content exceeds 0.050%. Therefore, the P content is set to 0.050% or less. The P content is preferably 0.040% or less, and more preferably 0.030% or less. The lower limit of the P content is not particularly limited. However, since excessive de-P leads to an increase in costs, the P content is preferably 0.010% or more.

[0032] S: 0.010% or less S is an element that is inevitably contained in steel. Excessive S content, particularly S content exceeding 0.010%, promotes the precipitation of MnS and reduces corrosion resistance. Therefore, the S content is set to 0.010% or less. Preferably, the S content is 0.005% or less. There is no particular lower limit for the S content. However, since excessive de-S leads to increased costs, the S content is preferably 0.001% or more.

[0033] Cr: 16.00~22.00% Cr is an element effective in ensuring corrosion resistance. If the Cr content is less than 16.00%, sufficient corrosion resistance cannot be obtained after brazing. However, if the Cr content exceeds 22.00%, a Cr oxide film is formed on the surface of the stainless steel during brazing, and the brazing property is reduced. Therefore, the Cr content is set to a range of 16.00 to 22.00%. The Cr content is preferably 16.50% or more, and more preferably 17.00% or more. Moreover, the Cr content is preferably 19.50% or less, and more preferably 19.00% or less.

[0034] Ni: 3.00~15.00% Ni is an important element in the present invention. As described above, by appropriately controlling the Ni content, the bond energy value between solid (base stainless steel) atoms and the bond energy value between liquid (Ni brazing material) atoms approach each other. As a result, excellent Ni brazing properties are obtained. Therefore, the Ni content is set to 3.00% or more. On the other hand, if the Ni content exceeds 15.00%, the hot workability and cold workability decrease. Therefore, the Ni content is set to the range of 3.00 to 15.00%. The Ni content is preferably 4.00% or more, more preferably 6.00% or more. Moreover, the Ni content is preferably 10.00% or less, more preferably 7.00% or less.

[0035] Al: 0.100% or less Al is an element useful for deoxidization. Such an effect is preferably obtained by containing 0.001% or more of Al. However, if the Al content exceeds 0.100%, Al-enriched substances such as Al oxides and Al nitrides are likely to be formed on the surface of the stainless steel during brazing. As a result, brazing properties are reduced. Therefore, the Al content is set to 0.100% or less. The Al content is preferably 0.040% or less, and more preferably 0.015% or less.

[0036] N: 0.001 to 0.300% N enhances corrosion resistance and strength. To obtain such effects, the N content is set to 0.001% or more. On the other hand, if the N content exceeds 0.300%, the excess N becomes a cause of blowholes during casting or welding. Therefore, the N content is set to the range of 0.001 to 0.300%. The N content is preferably 0.003% or more. Moreover, the N content is preferably 0.010% or less, and more preferably 0.005% or less.

[0037] Ni / (Si+Mn+0.08×Cr+Al)≧2.30 (1) In the formula, Si, Mn, Cr, Ni, and Al are the contents (mass%) of Si, Mn, Cr, Ni, and Al in the composition, respectively. As described above, in order to improve Ni brazeability, it is important to appropriately control the Ni content so as to satisfy the relationship of the above formula (1) according to the Si, Mn, Cr and Al contents. That is, by optimizing the composition of the stainless steel as the base material as described above and satisfying the above formula (1), the value of the bond energy between solid atoms and the value of the bond energy between liquid atoms become closer. As a result, excellent Ni brazeability is obtained. Therefore, the composition of the stainless steel as the base material is optimized, in particular, the contents of Si, Mn, Cr, Ni and Al are set within the above ranges, and Ni / (Si+Mn+0.08×Cr+Al) is set to 2.30 or more. Ni / (Si+Mn+0.08×Cr+Al) is preferably 2.50 or more, more preferably 4.00 or more, and even more preferably 5.00 or more.

[0038] The basic component composition of the stainless steel according to one embodiment of the present invention has been described above, but it may further contain one or more elements selected from the following elements. Mo: 3.00% or less, Cu:3.00% or less, Ti: 0.50% or less, Nb: 0.50% or less, V: 0.20% or less, Zr: 0.10% or less, Sn: 0.50% or less, B: 0.0100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, Ta: 0.10% or less and REM: 0.10% or less

[0039] Mo: 3.00% or less Mo stabilizes the passivation film of stainless steel to improve corrosion resistance. To obtain such an effect, it is preferable that the Mo content is 0.01% or more. On the other hand, if the Mo content exceeds 3.00%, the high-temperature strength increases and the hot workability is likely to decrease. Furthermore, surface defects are likely to occur during hot rolling. Therefore, when Mo is contained, the content is preferably 3.00% or less. The Mo content is more preferably 0.60% or less, and further preferably 0.40% or less.

[0040] Cu:3.00% or less Cu has the effect of enhancing corrosion resistance. In order to obtain such an effect, it is preferable that the Cu content is 0.01% or more. The Cu content is more preferably 0.30% or more, and further preferably 0.50% or more. On the other hand, if the Cu content exceeds 3.00%, the high-temperature strength increases and the hot workability is likely to decrease. Therefore, when Cu is contained, the content is preferably 3.00% or less. The Cu content is more preferably 1.50% or less, and further preferably 1.20% or less.

[0041] Ti: 0.50% or less Ti has the effect of increasing the strength of steel. In addition, Ti also has the effect of preventing sensitization by bonding with C and N contained in steel. In order to obtain such an effect, it is preferable that the Ti content is 0.01% or more. The Ti content is more preferably 0.03% or more, and further preferably 0.05% or more. On the other hand, if the Ti content exceeds 0.50%, an oxide film may be formed on the surface of the stainless steel during brazing, and the brazing property may be deteriorated. Therefore, when Ti is contained, the content is preferably 0.50% or less. The Ti content is more preferably 0.20% or less, and further preferably 0.10% or less.

[0042] Nb: 0.50% or less Nb, like Ti, has the effect of increasing the strength of steel. In addition, Nb also has the effect of preventing sensitization by bonding with C and N contained in steel. In order to obtain such an effect, it is preferable that the Nb content is 0.01% or more. The Nb content is more preferably 0.03% or more, and further preferably 0.05% or more. On the other hand, if the Nb content exceeds 0.50%, an oxide film may be formed on the surface of the stainless steel during brazing, and the brazing property may be deteriorated. Therefore, when Nb is contained, the content is preferably 0.50% or less. The Nb content is more preferably 0.20% or less, and further preferably 0.10% or less.

[0043] V: 0.20% or less Like Ti and Nb, V combines with C and N contained in the steel and has the effect of preventing sensitization. In order to obtain such an effect, it is preferable that the V content is 0.01% or more. On the other hand, if the V content exceeds 0.20%, the workability is likely to decrease. Therefore, when V is contained, the content is preferably 0.20% or less. The V content is more preferably 0.10% or less.

[0044] Zr: 0.10% or less Like Ti and Nb, Zr combines with C and N contained in the steel and has the effect of preventing sensitization. In order to obtain such an effect, it is preferable that the Zr content is 0.01% or more. On the other hand, if the Zr content exceeds 0.10%, the workability is likely to decrease. Therefore, when Zr is contained, the content is preferably 0.10% or less. The Zr content is more preferably 0.05% or less.

[0045] Sn: 0.50% or less Sn is an element effective in suppressing surface roughness during rolling. In order to obtain such an effect, it is preferable that the Sn content is 0.01% or more. On the other hand, if the Sn content exceeds 0.50%, the hot workability is likely to decrease. Therefore, when Sn is contained, the content is preferably 0.50% or less. The Sn content is more preferably 0.20% or less, and further preferably 0.10% or less.

[0046] B: 0.0100% or less B is an element that improves hot workability. In order to obtain such an effect, it is preferable that the B content is 0.0003% or more. On the other hand, if the B content exceeds 0.0100%, there is a risk of causing a decrease in corrosion resistance. Therefore, when B is contained, the content is preferably 0.0100% or less. The B content is more preferably 0.0030% or less.

[0047] Ca:0.0100% or less Ca improves the penetration of the welded portion and improves the weldability. In order to obtain such an effect, it is preferable that the Ca content is 0.0005% or more. On the other hand, if the Ca content exceeds 0.0100%, Ca and S are bonded to generate CaS, which may reduce the corrosion resistance. Therefore, when Ca is contained, the content is preferably 0.0100% or less. The Ca content is more preferably 0.0050% or less, and further preferably 0.0020% or less.

[0048] Mg: 0.0100% or less Mg acts as a deoxidizer. To obtain such an effect, it is preferable that the Mg content is 0.0005% or more. On the other hand, if the Mg content exceeds 0.0100%, the toughness of the steel decreases, and the manufacturability decreases. Therefore, when Mg is contained, the content is preferably 0.0100% or less. The Mg content is more preferably 0.0050% or less, and further preferably 0.0020% or less.

[0049] Ta: 0.10% or less Ta is an element that improves hot workability. In order to obtain such an effect, it is preferable that the Ta content is 0.01% or more. On the other hand, if the Ta content exceeds 0.10%, the corrosion resistance may decrease. Therefore, when Ta is contained, the content is preferably 0.10% or less. The Ta content is more preferably 0.05% or less.

[0050] REM: 0.10% or less REM is an element that improves hot workability. In order to obtain such an effect, it is preferable that the REM content is 0.01% or more. On the other hand, if the REM content exceeds 0.10%, the corrosion resistance may decrease. Therefore, when REM is contained, the content is preferably 0.10% or less. The REM content is more preferably 0.05% or less. Here, REM means Sc, Y, and lanthanoid elements (elements with atomic numbers of 57 to 71, such as La, Ce, Pr, Nd, and Sm). Here, the REM content is the total content of these elements.

[0051] The balance other than the above elements in the composition of the stainless steel according to one embodiment of the present invention is Fe and inevitable impurities. Note that, for the above-mentioned Mo, Cu, Ti, Nb, V, Zr, Sn, B, Ca, Mg, Ta and REM, when the content of each element is less than the respective preferable lower limit, the element is treated as an inevitable impurity.

[0052] The shape of the stainless steel according to one embodiment of the present invention is not particularly limited, but examples include a plate shape (steel plate), a tube shape (steel pipe), and a rod shape (round bar material, square bar, etc.). The thickness (outer diameter in the case of a round bar material) is preferably 0.3 to 5.0 mm, and more preferably 0.8 to 2.0 mm.

[0053] In addition, the stainless steel according to one embodiment of the present invention is a stainless steel used for Ni brazing, that is, as a base material (joined material) for Ni brazing. Here, Ni brazing is brazing using a Ni brazing material as a brazing material. The Ni brazing material is an alloy having a composition of Ni: 50 mass% or more. The Ni brazing material is an alloy having a composition of Ni: 70 mass% or more, more preferably Ni: 80 mass% or more. The composition of the Ni brazing material may contain other elements, for example, at least one element selected from Cr, B, Si, Fe, C, and P, for the purpose of adjusting the melting point. A more specific composition of the Ni brazing material may be, for example, the composition of nickel brazing material specified in JIS Z 3265:1998. The form of use of the Ni brazing material is not particularly limited, but is preferably, for example, a paste (a mixture of powdered Ni brazing material and a binder composed of an organic substance). In the paste-like Ni brazing material, the mass mixing ratio of the binder to the Ni brazing material (=[mass of binder] / [mass of Ni brazing material]×100) is preferably 5 to 30%, more preferably 10 to 20%, by mass. Note that the binder made of an organic substance volatilizes during Ni brazing.

[0054] Moreover, the stainless steel according to one embodiment of the present invention is particularly suitable for use in water heaters and heat exchangers, which will be described later.

[0055] [2] Joints, water heaters, and heat exchangers Next, a joint body, a water heater, and a heat exchanger according to an embodiment of the present invention will be described.

[0056] A joint according to one embodiment of the present invention comprises the stainless steel [1] above, a metal material, and a joint (hereinafter simply referred to as the joint) of Ni brazing material that joins the stainless steel and the metal material.

[0057] Here, the stainless steel described above in [1] is the base material.

[0058] The metal material is a base material (hereinafter, simply referred to as a mating material) of the stainless steel described in [1] above, which is the base material. That is, the metal material is a material that is joined to the stainless steel described in [1] above, and examples of the metal material include stainless steel, copper, alloys such as copper alloys and nickel alloys, carbon steel, and alloy steel. Among them, stainless steel, copper, and copper alloys are preferable. The metal material may be the stainless steel described in [1] above. In other words, the joint may be a joint between the stainless steels described in [1] above.

[0059] The joint is formed by solidifying the Ni brazing material melted during brazing. Therefore, it can be said that the joint has a composition of Ni: 50 mass% or more, similar to the composition of the Ni brazing material described above. In addition to Ni, the composition of the joint may contain at least one element selected from Cr, B, Si, Fe, C, and P, or an element derived from the stainless steel base material or the metallic material of the mating material.

[0060] When the joined body according to the embodiment of the present invention has a plurality of joined parts, at least one of them should be a joined part made of Ni brazing material.

[0061] Moreover, the water heater and the heat exchanger according to the embodiment of the present invention have a joint according to the embodiment of the present invention, for example, as a joint between pipes or a joint between a pipe and a tube sheet. Here, the joint between pipes and the joint between a pipe and a tube sheet correspond to the stainless steel and the metal material (base material and mating material) in [1] above, respectively.

[0062] Examples of the water heater include a gas water heater, an electric water heater, and a latent heat recovery water heater. Examples of the heat exchanger include a water heater, an exhaust heat recovery device, and a heat exchanger of an exhaust gas recirculation device.

[0063] [3] Stainless steel manufacturing method Next, a preferred method for producing stainless steel according to one embodiment of the present invention will be described taking as an example the case of producing a plate-shaped stainless steel (hereinafter also referred to as a stainless steel plate). First, a steel material (steel slab) having the above-mentioned composition is hot-rolled to obtain a hot-rolled steel sheet of a predetermined thickness. Then, the hot-rolled steel sheet is optionally subjected to hot-rolled sheet annealing to obtain a hot-rolled annealed steel sheet. Then, the hot-rolled steel sheet or the hot-rolled annealed steel sheet is cold-rolled to obtain a cold-rolled steel sheet of a predetermined thickness. Then, the cold-rolled steel sheet is subjected to cold-rolled sheet annealing to obtain a cold-rolled annealed steel sheet. In this way, a stainless steel sheet having the above-mentioned composition can be manufactured. Note that the conditions of hot rolling, cold rolling, hot-rolled sheet annealing, cold-rolled sheet annealing, etc. are not particularly limited, and may be in accordance with a conventional method.

[0064] For example, in the steelmaking process for producing steel, it is preferable to perform secondary refining of steel melted in a converter or electric furnace by the VOD method or the like to produce steel having the above-mentioned composition. The produced molten steel can be made into a steel material by a known method. In terms of productivity and quality, a continuous casting method is preferable. Next, the steel material is heated to preferably 1050 to 1250°C, and hot-rolled into a hot-rolled steel sheet of a predetermined thickness by hot rolling. Next, the above-mentioned hot-rolled steel sheet is optionally subjected to continuous annealing at a temperature of 900 to 1150°C, and then optionally descaled by pickling or the like to produce a hot-rolled annealed steel sheet. Furthermore, optionally, scale may be removed by shot blasting before pickling.

[0065] The hot-rolled steel sheet or hot-rolled annealed steel sheet may be subjected to cold rolling. The number of cold rolling may be one. From the viewpoint of productivity and required quality, the number of cold rolling may be two or more with intermediate annealing in between. The total rolling reduction in cold rolling is preferably 60% or more, more preferably 70% or more. Next, the cold-rolled steel sheet obtained by cold rolling is optionally subjected to continuous annealing (finish annealing) at a temperature of preferably 900 to 1150°C, more preferably 950 to 1150°C, and then optionally pickled to obtain a cold-rolled annealed steel sheet. Note that the continuous annealing may be performed by bright annealing, and pickling may be omitted. Furthermore, depending on the application, after the finish annealing, skin pass rolling or the like may be performed to adjust the shape, surface roughness and material properties of the steel sheet.

[0066] In the above example, the manufacturing method for forming a plate shape was described as an example, but hot working and cold working can also be performed in addition to forming a plate shape. In this case, the conditions for hot working and cold working are not particularly limited, and may be in accordance with a conventional method.

[0067] [4] Ni brazing Next, the joined body according to one embodiment of the present invention described above in [2], and Ni brazing performed when manufacturing (assembling) a water heater and a heat exchanger will be described.

[0068] Ni brazing, for example, uses a vacuum furnace or atmospheric furnace, and the degree of vacuum is 4.0 × 10 -3It is preferable to carry out the brazing in a vacuum atmosphere or a nitrogen atmosphere at a pressure of 60 Pa or less. The brazing temperature is not particularly limited, but 900 to 1100 ° C is preferable. If the holding time at the brazing temperature is too short, the brazing material does not spread sufficiently. On the other hand, if the holding time at the brazing temperature is too long, an oxide film may grow on the surface of the stainless steel as the base material, and the brazing property may be reduced. Therefore, the brazing time is preferably 5 to 60 minutes. The Ni brazing material, the stainless steel as the base material [1], and the metal material as the mating material are as described above. In this way, the joined body according to one embodiment of the present invention in [2], as well as the water heater and the heat exchanger can be manufactured by Ni brazing the stainless steel as the base material [1] and the metal material as the mating material. Other manufacturing steps may be performed according to ordinary methods. EXAMPLES

[0069] Steel having the composition shown in Table 1 (the balance being Fe and unavoidable impurities) was melted in a vacuum melting furnace. The steel was then heated at 1100 to 1200°C for 1 hour and hot rolled to obtain a hot-rolled steel sheet having a thickness of 4.0 mm. The hot-rolled steel sheet was then annealed in a temperature range of 950 to 1100°C to obtain a hot-rolled annealed steel sheet. The hot-rolled annealed steel sheet was then mechanically ground to remove scale, and then cold rolled to obtain a cold-rolled steel sheet having a thickness of 1.0 mm. The cold-rolled steel sheet was then finish-annealed in a temperature range of 950 to 1100°C to obtain a cold-rolled annealed steel sheet. The surface of the obtained cold-rolled annealed steel sheet was polished with emery paper up to No. 800 and degreased with acetone to obtain a stainless steel as a test material.

[0070] The stainless steels thus obtained were evaluated for Ni brazability in the following manner. The chemical compositions of the test stainless steels were substantially the same as those of the steels listed in Table 1, and all of the inventive examples satisfied the above-mentioned ranges of chemical composition.

[0071] (Evaluation of Ni brazing properties) A test piece with a width of 50 mm and a length of 50 mm was cut out from the above stainless steel (cold-rolled annealed steel sheet). Then, 0.1 g of a paste-like Ni brazing material was placed in a circle with a diameter of 5 mm on the surface of the test piece. The paste-like Ni brazing material was a mixture of powdered Ni brazing material (BNi-2 (JIS Z 3265:1998)) and a binder composed of an organic substance. The mass mixing ratio of the binder to the Ni brazing material was 10% by mass. Then, the test piece was placed horizontally in a vacuum furnace, and the vacuum furnace was evacuated. Then, nitrogen gas was introduced into the vacuum furnace. Then, the vacuum furnace was heated, and the test piece was held in a nitrogen atmosphere at 1050°C and 40 Pa for 10 minutes. Then, it was cooled to room temperature, and the circle equivalent diameter of the Ni brazing material on the surface of the test piece was measured. Then, the spread rate of the Ni brazing material was calculated by the following formula, and the Ni brazeability was evaluated according to the following evaluation criteria. The evaluation results are shown in Table 1. [Spreadability of Ni brazing material (%)] = [Circle equivalent diameter of Ni brazing material on the surface of the test piece after heating (mm)] ÷ [Circle equivalent diameter of Ni brazing material on the surface of the test piece before heating (mm)] × 100 Evaluation criteria Excellent (Pass): The spread rate of Ni-containing brazing material is 150% or more. Insufficient (failed): The spread rate of the Ni-containing brazing filler metal is less than 150%.

[0072] [Table 1]

[0073] As shown in Table 1, all of the stainless steels of the invention examples exhibited excellent Ni brazeability.

[0074] On the other hand, in the comparative examples, sufficient Ni brazeability was not obtained. That is, in Comparative Example No. 19, the Si content exceeded the upper limit, and therefore sufficient brazeability was not obtained. In Comparative Example No. 20, the Cr content exceeded the upper limit, and therefore sufficient brazeability was not obtained. In Comparative Example No. 21, the Al content exceeded the upper limit, and therefore sufficient brazeability was not obtained. In Comparative Example No. 22, the Mn content exceeded the upper limit, and therefore sufficient brazeability was not obtained. In Comparative Example No. 23, the Ni content was below the lower limit and did not satisfy the above formula (1), so sufficient brazeability was not obtained. In Comparative Example No. 24, the above formula (1) was not satisfied, and therefore sufficient brazeability was not obtained. [Industrial Applicability]

[0075] The stainless steel according to one embodiment of the present invention has excellent Ni brazing properties, and is therefore particularly suitable for use in water heaters and heat exchangers that are assembled using Ni brazing.

Claims

1. In mass percent, C: 0.001-0.050%, Si: 0.01 to 0.50%, Mn: 0.01-0.50%, P: 0.050% or less, S: 0.010% or less, Cr: 16.00-22.00%, Ni: 3.00-8.71%, Al: 0.100% or less; N: 0.001-0.300%, and the balance being Fe and unavoidable impurities, A stainless steel for Ni brazing that satisfies the following formula (1): Ni / (Si+Mn+0.08×Cr+Al)≧2.30 (1) In the formula, Si, Mn, Cr, Ni and Al are the Si, Mn, Cr, Ni and Al contents (mass%) in the component composition, respectively.

2. The composition further comprises, in mass%, Mo: 3.00% or less, Ti: 0.50% or less, Nb: 0.50% or less, V: 0.20% or less, Zr: 0.10% or less, Sn: 0.50% or less, B: 0.0100% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, Ta: 0.10% or less and REM: 0.10% or less The stainless steel for Ni brazing according to claim 1, which contains one or more selected from the following:

3. The stainless steel for Ni brazing according to claim 1 or 2, A metal material; a joint between the stainless steel for Ni brazing and the metal material, and a Ni brazing material; A zygote that has the following functions.

4. A heat exchanger comprising the assembly according to claim 3.

5. A water heater comprising the joint according to claim 3.

Citation Information

Patent Citations

  • Stainless steel with superior wetting property for molten metal

    JP1981081660A

  • Stainless steel for high purity gas, excellent in machinability

    JP1995026349A

  • Stainless steel for high purity gas excellent in dust producing resistance at the time of welding

    JP1995173580A

  • Austenitic stainless steel excellent in molten salt corrosion resistance in chloride environment

    JP2000319761A

  • Stainless steel for brazing and brazing method

    JP2010065278A